Facial Feature Tracking Using Efficient Particle Filter and Active Appearance Model. (25th September 2014) - Cho, Durkhyun; Lee, Sanghoon; Suh, Il Hong
For natural human-robot interaction, the location and shape of facial features in a real environment must be identified. One robust method to track facial features is by using a particle filter and the active appearance model. However, the processing speed of this method is too slow for utilization in practice. In order to improve the efficiency of the method, we propose two ideas: (1) changing the number of particles situationally, and (2) switching the prediction model depending upon the degree of the importance of each particle using a combination strategy and a clustering strategy. Experimental results show that the proposed method is about four times faster than the conventional method using a particle filter and the active appearance model, without any loss of performance.